Geometria esférica: uma sequência didática para a aprendizagem de conceitos elementares no ensino básico - Andrade, Maria Lúcia Torelli Doria de (2011)
The objective of the current work is to investigate ownership of Spherical Geometry elementary concepts by students in the second year of high school, from a teaching sequence. In addition, it aimed to solve the activities of this sequence, the subjects carry out research treatments and Semiotic Registers Representation conversions relevant to the mathematical Spherical Geometry objects to be studied. We seek to answer the following question: How a didactic sequence articulating different Registers Representation can evaluate high school students in learning Spherical Geometry concepts? Therefore, we applied to two high school students teaching sequence. We based it on Raymond Duval s Semiotic Registers Representation Theory and Guy Brousseau s Didactic Situations Theory as theoretical foundation of this research. The research approach was qualitative and, as methodology we adopted Engineering Curriculum assumptions. Watching the subjects research production in the course of the activities sequence, we found out these individuals performed conversions and registers treatments by semiotic representation according to Duval (2009), as well as they did the record conversion in natural language (activity statement) to record material (Styrofoam ball), which led them to solve the activity and understand Spherical Geometry straight line concept. In this sense, we could highlight semiotic representation material record, and infer that it contributed to the concepts ownership required by the research subjects